New Insights into Fertilisation with Animal Manure for Annual Double-Cropping Systems in Nitrate-Vulnerable Zones of Northeastern Spain - Dolores Quilez; Monica Guillén; Marta Vallés; Arturo Daudén; Beatriz Moreno-García (Agronomy)
Maize double-cropping production systems in Mediterranean areas have a great nitrogen extraction capacity and high nitrogen (N) requirements. This study aims to assess whether in these farming systems, animal manure can be applied, using adequate management practices, at levels exceeding the maximum annual amount of livestock manure established in the European Nitrate Directive for vulnerable zones (170 kg N ha−1) without increasing the risk of water nitrate contamination. We compare the risk of nitrate leaching under two fertilisation strategies, one with synthetic fertilisers and the second with a maximised application of pig slurry, exceeding the limits of the EU Nitrate Directive, in two soil types. Crop yields, N extraction and nitrate concentrations below the crop root zone were not affected by the fertilisation strategies at each site. The results show that pig slurry can be applied above the limit of 170 kg N ha−1 under the conditions of the study, up to 360 kg N ha−1, without increasing the risk for nitrate leaching.